Co-management of protected areas to alleviate conservation conflicts: Experiences in Norway. - Fedreheim, Gunn Elin; Blanco, Ester (International Journal of the Commons, 2017)
Source at: https://doi.org/10.18352/ijc.749 This paper addresses the perceptions of actors of protected areas in Norway about a co-management regime at the local level. The analysis is based on quantitative data from surveys of actors of eight protected areas in northern Norway. The surveys were undertaken just before a change to co-management in 2010. The results show that the two strongest determinants that explain actors’ initial support of the governance change as a means to alleviate conflict are (i) the relationship of actors to the protected areas in terms of knowledge of the protected areas and mental models on conservation and (ii) the economic relevance of the areas for them. Traditionally, other sociocultural variables such as indigenous background (Sámi), age, and gender have been considered relevant and were also identified as significant attributes that define preferences for conservation management alternatives. We build on the quantitative findings on actors’ perceptions to develop a broader discussion on the relationship of the new management model for protected areas implemented and conflict resolution on land conservation in the country.